Perpetual Peace: An Analysis of Kant - Alfiansyah, Iqbal Maulana; Latief, Mohamad; Taslim, Naqia Salsabila (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2022)
This study critically discussed the concept of 'perpetual peace' according to Immanuel Kant. For Kant, peace is absolute, and war must be avoided. Kant's concept of peace departs from his philosophical ideas about humans and ethics. According to the researcher's hypothesis, Kant's concept of peace is problematic and not compatible with the concept of peace in Islam. This study aimed to describe Immanuel Kant's concept of perpetual peace and the concept of peace in Islam. In addition, it also analyzed how Kant's concept of perpetual peace is viewed from the Islamic worldview. This research was library research, and the methods used were descriptive, analytical, and comparative. This research concluded that Kant's concept of peace had several philosophical and practical problems. Philosophically, Kant's concept of peace revolves around the concept of man, ethics, and causality, which tend to deny the element of God in it. In practical terms, Kant's idea that war should not exist is a dream that is difficult to realize. His opinion about the peace triangle also leaves many problems.